2017
DOI: 10.1007/s00114-017-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil N-fixing bacteria communities to invasive plant species under different types of simulated acid deposition

Abstract: Biological invasions have incurred serious threats to native ecosystems in China, and soil N-fixing bacteria communities (SNB) may play a vital role in the successful plant invasion. Meanwhile, anthropogenic acid deposition is increasing in China, which may modify or upgrade the effects that invasive plant species can cause on SNB. We analyzed the structure and diversity of SNB by means of new generation sequencing technology in soils with different simulated acid deposition (SAD), i.e., different SO to NO rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In addition, extensive research by our group on quantifying the relationship between plant invasion and N deposition and P stress in terrestrial ecosystems has shown that plant invasion and N deposition change the soil N-fixative bacteria (SNB) community structure by enhancing the ecological characteristics of soil microbial communities (such as nifH gene abundance), altering pH and other soil physicochemical properties and especially increasing the total number of SNB species. Bioavailability of N was increased in soil as a result of the combined effects of SNB and the acidification of deposited N and, thus, invasion by alien plants was accelerated [78,79]. Similarly, woody invasive alien plants may have higher resource capture ability as well as higher relative growth rates from reduced material investment in leaves per unit area under N deposition [80].…”
Section: Mechanisms Of N and P Promote Alien Plant Invasionmentioning
confidence: 99%
“…In addition, extensive research by our group on quantifying the relationship between plant invasion and N deposition and P stress in terrestrial ecosystems has shown that plant invasion and N deposition change the soil N-fixative bacteria (SNB) community structure by enhancing the ecological characteristics of soil microbial communities (such as nifH gene abundance), altering pH and other soil physicochemical properties and especially increasing the total number of SNB species. Bioavailability of N was increased in soil as a result of the combined effects of SNB and the acidification of deposited N and, thus, invasion by alien plants was accelerated [78,79]. Similarly, woody invasive alien plants may have higher resource capture ability as well as higher relative growth rates from reduced material investment in leaves per unit area under N deposition [80].…”
Section: Mechanisms Of N and P Promote Alien Plant Invasionmentioning
confidence: 99%
“…Nitrogen-fixing bacteria in the soil can promote the uptakes of nitrogen (N), phosphorus (P), potassium (K), and other nutrients by plants in the nitrogen-fixing symbiotic relationship. Since N, P, K, and other elements are key nutrients that influence plant growth and reproduction, nitrogen-fixing bacteria can influence the expansion of the growth range of plant communities [ 23 ]. Hence, the types and functions of soil bacteria regulate plant community structure and function, as well as evolutionary processes in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…; Wang et al . ). Thus, changes in soil fungal communities in this study may be governed by other factors, which do not support the first hypothesis of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Soil pH was measured in situ using a digital soil acidity–moisture meter (ZD‐06, ZD Instrument, Taizhou, China; Wang et al . , ,b,d). Soil electrical conductivity was measured in situ using a digital soil electrical conductivity tester (ZD‐EC; Kamiyama et al .…”
Section: Methodsmentioning
confidence: 99%